Pengaruh metode game pada perkembangan belajar Bahasa Arab siswa - Nimran, Jihan Aulia (Maliki Interdisciplinary Journal, 2024)
This research aims to describe the influence of game methods on students Arabic language learning development. How do students' Arabic learning progress when the teacher uses the game method in learning Arabic. This research uses descriptive qualitative research, which aims to describe of an event or occurrence and clarify a phenomenon that occurs. In this research, a literature study was carried out by collecting data based on existing literature, such as collecting library data, reading, taking notes, and analyzing books and journals that were relevant to the problem being discussed. The results of this research show that (1) Learning methods must adapt to each individual student's abilities and background. (2) The use of game methods in learning Arabic makes students more active in learning and can stimulate enthusiasm and motivation for learning in students. (3) Student learning development is influenced by internal psychological factors of student and external factors in the form of teachers and family environment.